PENGARUH PEMBERIAN ASI TERHADAP PERKEMBANGAN ANAK USIA 6 - 12 BULAN DI RW 04 DESA SAMBIBULU KECAMATAN TAMAN SIDOARJO - F Firdaus; Ayun Nif'ah (Universitas Nahdlatul Ulama Surabaya, 2015)
This research is to observe the purpose of this study was to analyze the influence of breastfeeding toward the development of children aged 6 - 12 months living in RW 04 Sambibulu Village, Taman Sub-district, Sidoarjo. The design of  research was analytic  retrospective  study. The population involved 29 couples with their children aged 6  -  12 months living in the above mentioned region. The simple random sampling technique was used to take 27 couples as the samples of research. The independent variable of this research was breastfeeding, whereas the dependent one was  the child's development. Questionnaires of breast and checklist of KPSP (Pre Screening Questionnaire for Child Development) were used to collect the data which analyzed by using Mann-Whitney's statistic test with the significance level α = 0.05, it means that there was a relationship between breastfeeding and  the development of children p (0.000) < α (0.05)